Handbook of Statistics on Indian Securities Market 2013 - Securities and Exchange Board of India (Mumbai: SEBI)
The handbook presents the statistics of the domestic securities market in a lucid form with monthly and annual series till December 2013. Besides, annual data on International Securities Markets have also been covered for the benefit of users. The handbook has been compiled with data sources from SEBI along with other institutions viz. RBI, Exchanges, Depositories, Credit Rating Agencies, World Federation of Exchanges and others.
Part I : Securities Market (Annual Series) -- Part II : Securities Market (Monthly Series) -- Part III : International Securities Market
Keywords: Securities Market - India; Securities Market - International